Viability of BHK-21 Fibroblast Cells Resulting from Synthesis of Collagen Powder (Thunnus albacares) with Variation of NaCl Concentration - Zefanya, Kartika; Rahmitasari, Fitria; Widaningsih, Widaningsih; Prananingrum, Widyasri (Odonto : Dental Journal, 2024)
Background: Collagen plays a crucial role in post-extraction wound healing. Thunnus albacares skin, a collagen source synthesized through the papain soluble collagen (PaSC) method with varying NaCl concentrations, is assessed for non-toxicity using the MTT assay on BHK-21 fibroblast cell cultures. This research is to determine cell viability resulting from synthesizing collagen powder from the skin of yellowfin tuna (Thunnus albacares) with varying NaCl concentrations using the papain soluble collagen (PaSC) method. Method: Collagen powder was synthesized by cleaning Thunnus albacares skin measuring 1x1 cm, soaking it in 0.1 M NaOH, hydrolyzing it with CH3COOH, extracting it with papain enzyme, and then dividing the samples into four groups: without NaCl, NaCl 0.9 M, NaCl 1.3 M, and NaCl 1.7 M. Samples were centrifuged (6000 rpm) and followed by freeze-drying. Cell viability was obtained by conducting a cytotoxicity test using the MTT Assay method on BHK-21 fibroblast cells. Result: The percentage of cell viability in groups K, P1, P2, P3, and P4 were 100%, 10.708%, 113.750%, 107.833%, and 105.958%, respectively. The Kruskall-Wallis test yielded a significance value 0.000, indicating a significant difference (p<0,005). The Mann-Whitney test confirmed significant differences between groups. Conclusion: Collagen powder from Thunnus albacares skin with NaCl concentrations of 0.9 M, 1.3 M, and 1.7 M showed no toxic effects, while the group without NaCl showed toxic effects. Collagen powder with a NaCl concentration of 1.7 M yielded ideal results and showed no toxic effects.